Webinar Industrial Talk: Emerging Technologies in ICT For Malaysia Industries in 2021 - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 3 June 2021 - Webinar Industrial Talk, with the title 'Emerging Technologies in ICT for Malaysia Industries in 2021' has been delivered by he Industry Advisory Panel at FK UMP, Wan Muzaffar Wan Hashim and moderated by Associate Professor Noraziah Ahmad, FK,UMP.